2013
DOI: 10.1371/journal.pone.0068820
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prolonged Storage of Red Blood Cells on Cancer Survival

Abstract: BackgroundThe duration of storage of transfused red blood cells (RBC) has been associated with poor clinical outcomes in some studies. We sought to establish whether prolonged storage of transfused RBC in cancer patients influences overall survival (OS) or cancer recurrence.Methods and FindingsPatients diagnosed with cancer at The Ottawa Regional Cancer Centre between January 01, 2000 and December 31, 2005 were included (n = 27,591) where 1,929 (7.0%) received RBC transfusions within one year from diagnosis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Nonetheless, Kaplan–Meier curves were nearly identical so that it is unlikely that the loss of statistical power debilitated the validity to detect a significant difference between patients receiving a transfusion of RBCs and patients that were not transfused. So far, there is still limited evidence to suggest to which extent transfusion of RBC that were stored for prolonged intervals may increase the risk for recurrent disease after cancer surgery . Finally, given a potential dose–response relationship between the number of transfused RBC units and the risk for a recurrent disease after cancer surgery, a median of 4 units of RBCs in the study population, and 2 units of RBCs in the matched cohort might have been insufficient to cause immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, Kaplan–Meier curves were nearly identical so that it is unlikely that the loss of statistical power debilitated the validity to detect a significant difference between patients receiving a transfusion of RBCs and patients that were not transfused. So far, there is still limited evidence to suggest to which extent transfusion of RBC that were stored for prolonged intervals may increase the risk for recurrent disease after cancer surgery . Finally, given a potential dose–response relationship between the number of transfused RBC units and the risk for a recurrent disease after cancer surgery, a median of 4 units of RBCs in the study population, and 2 units of RBCs in the matched cohort might have been insufficient to cause immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although cancer recurrence was significantly higher in patients who received erythrocyte transfusion than those who did not, this effect was not related to the duration of RBC storage. 24…”
Section: Rbc Storage and Tumour Progressionmentioning
confidence: 99%
“…Kekre et al. reviewed 27,000 cancer patients treated by means of chemoradiotherapy or surgery of whom 1929 had been transfused . Although the authors found significantly higher levels of cancer recurrence among transfused patients, there was no association with red cell storage duration (≤ 14 days vs. 14–28 days vs. > 28 days).…”
Section: Storage Of Packed Red Cellsmentioning
confidence: 99%
“…In cases of hepatocellular carcinoma, some authors claim a link between FFP administration and worsening overall survival [19], although others evaluating disease-free survival have demonstrated no effect [20]. been transfused [22]. Although the authors found significantly higher levels of cancer recurrence among transfused patients, there was no association with red cell storage duration (≤ 14 days vs. 14-28 days vs. > 28 days).…”
Section: Immunological Effectsmentioning
confidence: 99%